SCIENTIFIC APPROACH TO THE METHODS OF INCREASING THE LIFE CYCLE OF WHEELS OF RAILWAY VEHICLES (Transport systems and technologies, 2021)
The value of the life cycle of rolling stock wheels is determined by the frequency of maintenance, in the process of which the turning is carried out to restore the profiles of the rolling surfaces, or the replacement of completely worn wheels. Traffic safety depends on the technical condition of the wheels of locomotives and wagons. Maintenance and repair of wheelsets accounts for about 30% of all costs of Ukrzaliznytsia's rolling stock repair units. Wheel repair technologies are based on the complete restoration of wheel profiles by turning, using which, their life cycle is reduced, and costs increase by 20% or more. The railways of Ukraine use an outdated, unreasonable, inefficient system of control over the formation of rolling surfaces in operation. Therefore, there is a need to create a scientifically sound approach to methods of extending the life cycle of the wheels of locomotives and wagons while ensuring the safety of railway rolling stock. According to the proposed scientific approach, the wheel profile is restored to optimal parameters, which provides an extended life cycle of wheelsets. As a result of the developed scientific approach the life cycle of wheel pairs will increase by 15… 25% and the expenses of the railway for their repair will considerably decrease.
Keywords: wheel pair, life cycle, rolling stock, restoration, optimization, repair profile.